Innovative use of chitosan/ZnO NPs bio-nanocomposites for sustainable antimicrobial food packaging of poultry meat - Sasidharan, Shivitraloshini; Tey, Lai-Hock; Djearamane, Sinouvassane; Ab Rashid, Nor Khaizura Mahmud; PA, Rajeshwari; Rajendran, V.; Syed, Asad; Wong, Ling Shing; Santhanakrishnan, Vimaleswaran Karani; Asirvadam, Vijanth Sagayan; Antony Dhanapal, Anto Cordelia Tanislaus (Elsevier, 2024)
A novel nanocomposite was developed by integrating zinc oxide nanoparticles (ZnO NPs) into chitosan (CS) matrix and investigated for its impact on the quality and shelf life of refrigerated poultry meat over 11 days. Physicochemical properties including weight, pH, titratable acidity, color, thiobarbituric acid reactive substances assay, microbiological growth studies encompassed total psychotropic and mesophilic aerobic microorganisms, Enterobacteriaceae analyses, and zinc migration levels were conducted to determine the optimal nanocomposite concentration. Results revealed that bio-nanocomposite exhibited superior characteristics compared to chemogenic nanocomposite, chitosan, polyvinyl alcohol, and unwrapped meats. Bio-nanocomposite with reduced unsaturated lipid content extends poultry shelf life to 7 days in packaging, outperforming chemogenic-nanocomposites (5 days) and chitosan (4 days). This study proves that CS/ZnO NP nanocomposite is a promising active packaging material for meat, extending their shelf life without deteriorating its physicochemical characteristics and supporting sustainability, though further research on its toxicological properties is warranted. © 2024 The Authors